The role and importance of taxes as one of the sources of state budget income - Lubaś, Magdalena (Journal of Finance and Financial Law, 2019)
At present, no one can imagine an economy without taxes. Everyone consumes, uses various services, achieves income from various sources owns property. It is these listed activities and a number of others that form the basis of taxation, from which a relevant tax is charged in an appropriate amount. The purpose of the article is to indicate the importance of tax in financing the state and the increase of revenues to the state budget from taxes over the years. It indicates what part of the state budget is tax and how the state and local government bodies used this type of tax. For this purpose, an analysis of the existing data presented on the website of the Ministry of Finance has been used.